Living gourd museum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
With support from the Japanese International Cooperation Agency, Kenya has established the world s first gourd museum, annex documentation centre and genebank. Gourds Lagenaria siceraria and Luffa cylindrica also known as African calabashes were...